1989
DOI: 10.2337/diacare.12.3.173
|View full text |Cite
|
Sign up to set email alerts
|

Taste Impairment and Related Factors in Type I Diabetes Mellitus

Abstract: To study taste in type I (insulin-dependent) diabetes mellitus, 57 consecutive diabetic outpatients (mean +/- SE duration of diabetes 11.4 +/- 0.4 yr) and 38 control subjects were screened for taste disorders with electrogustometry and chemical gustometry. Both groups were comparable for all subject characteristics except body mass index, which was higher in the diabetic group (P less than .05). A taste impairment was found in the diabetic group relative to the control group with electrogustometry (mean thresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(120 citation statements)
references
References 0 publications
7
108
2
Order By: Relevance
“…[6] In the present study, Group I showed decreased detection threshold for sweet, salty, and sour taste. In Group II, the participants responded to the lower concentrations of the taste solutions (sweet, salty, and sour) when concentrations to Group I and Group III, the participants responded to lowest concentrations of the taste solutions which implies that was perceived in lower concentrations in all the three groups.…”
Section: Discussionsupporting
confidence: 49%
“…[6] In the present study, Group I showed decreased detection threshold for sweet, salty, and sour taste. In Group II, the participants responded to the lower concentrations of the taste solutions (sweet, salty, and sour) when concentrations to Group I and Group III, the participants responded to lowest concentrations of the taste solutions which implies that was perceived in lower concentrations in all the three groups.…”
Section: Discussionsupporting
confidence: 49%
“…However, hypertension and drugs commonly used in diabetes, including sulfonylureas, metformin, and antihypertensive drugs, were not exclusion criteria. Alcohol and tobacco consumption was estimated as described previously (9)(10). Assessment of insulin dependence was based on clinical history and a plasma C-peptide <0.25 nM, 6 min after 1 mg of glucagon intravenously.…”
mentioning
confidence: 99%
“…Diabetes mellitus can cause a loss of the sweet taste sensation 64,65 in deed this may be present at time of diagnosis. Although the taste impairment is usually not severe, and is generally tolerated without complaint, the undiagnosed diabetic patient may favour sweet, sugary food hence exacerbating any hyperglycaemia.…”
Section: Taste Impairmentmentioning
confidence: 99%